Distortion and Its Representations in Contemporary Iraqi Visual Formation - Suhad Obaid Sabi (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The research aimed to identify distortion and its representations in contemporary Iraqi visual formation. The research sample consisted of three paintings by the plastic artist Alaa Bashir and the plastic artist Zahraa Al-Baghdadi. Among the most important findings: Distortion refers to a changed perspective in the visual arts, in which artworks appear distorted or stretched in a way that appears as if they were drawn by someone looking at them through a mirror or a curved lens. Perspective distortion uses distorted perspective to create the illusion of a different size, using the same size for each object or a single object much more significant than all the other objects in the image. In art, this can be used to create images that are taller or wider than they appear or to distort objects and make them appear larger or smaller. Some forms of distortion rely on unusual structural characteristics, such as deviating from correct anatomical proportions, distorting and distorting shapes, adopting perspective below the level of sight, relying on cold and neutral colors, and using straight, horizontal, slanted, and broken lines, among the most essential proposals: the necessity of conducting studies and research on modern Iraqi artistic production, its pessimistic and psychological suffering, the reasons for the emergence of these effects on it, and what is expressed in representations of distortion.